2018
DOI: 10.21512/lc.v12i1.3635
|View full text |Cite
|
Sign up to set email alerts
|

Impoliteness in EFL Complaints: Exploring its Intentions and Motivating Factors

Abstract: The present study investigated intentions and motivating factors of using impoliteness in interlanguage complaints by EFL learners. Empirical data were elicited by means of oral discourse completion tasks and questionnaires from 42 Indonesian learners of English. Post-structured interviews were conducted to obtain the intentions and reasons of deploying impoliteness in the complaints. The results reveal that impoliteness is triggered by three general motivating factors; speaker-related factors, target person-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
3
10
0
1
Order By: Relevance
“…It is in line with Kienpointner (in Wijayanto, Hikmat & Prasetyarini, 2018) that has reported that specific emotions can induce impoliteness. This also supports Spencer-Oatey (as cited in Wijayanto, Hikmat & Prasetyarini, 2018) who has averred that negative emotions can regulate linguistic behaviour. Self-emotion mismanagement which is how not being able to hold back anger can make the speaker be assessed as being impolite.…”
Section: (S3) Because I Will Straight Tell My Friends What I Want or Not To Dosupporting
confidence: 90%
See 1 more Smart Citation
“…It is in line with Kienpointner (in Wijayanto, Hikmat & Prasetyarini, 2018) that has reported that specific emotions can induce impoliteness. This also supports Spencer-Oatey (as cited in Wijayanto, Hikmat & Prasetyarini, 2018) who has averred that negative emotions can regulate linguistic behaviour. Self-emotion mismanagement which is how not being able to hold back anger can make the speaker be assessed as being impolite.…”
Section: (S3) Because I Will Straight Tell My Friends What I Want or Not To Dosupporting
confidence: 90%
“…It is found that male is frequently producing impolite utterance than female does. Regarding the impoliteness intention, a study carried out by Wijayanto, Hikmat and Prasetyarini (2018) reports that Indonesian learners of English frequently use harsh and explicit complaints. The studies have revealed inappropriate use of complaints by L2 learners.…”
Section: Introductionmentioning
confidence: 99%
“…According to Culpeper (1996), impoliteness can be used as "a means to an end rather than an end itself" (p. 146); hence, there are purposes of using impoliteness as teaching, equipping, grudge showing, power showing, counseling, warning, imposing, threatening, upholding to disciplines, developing a personality, to inrush, self-defending, gaining one's rights which Spencer-Oatey's (2002) called 'sociality rights,' etc. (Wijayanto et al, 2018). Culpeper (2011) proposed a framework for the conventionalized types of impoliteness formulas, which is particularly advantageous in empirical studies.…”
Section: Research Questionsmentioning
confidence: 99%
“…There are many pieces of research that analyzed impoliteness in many contexts. Culpeper (1996), for instance, investigated this concept in "army recruit training" (Wijayanto et al, 2018). He analyzed the intentions of impoliteness used by male officers toward female recruits.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Danish learners of English sound direct as they rarely use complaint modifications (Trosborg, 1995). Javanese learners of English frequently use rhetorical questions without incorporating hedges to mitigate them (Wijayanto, Prasetyarini, & Hikmat, 2014). Similarly, Indonesian learners of English rarely mitigate their complaints, particularly when they use rhetorical questions and imperative sentences to express accusations, blames, reproaches, and annoyance (Pratiwi, 2013).…”
Section: Research-article20172017mentioning
confidence: 99%